Immobilization of Bifidobacterium infantis Cells in Selected Hydrogels as a Method of Increasing Their Survival in Fermented Milkless Beverages - Urszula T. Jasińska; Sylwia Skąpska; Lubomiła Owczarek; Agnieszka Dekowska; Dorota Lewińska (Journal of Food Quality)
The aim of the study was to examine whether immobilization of Bifidobacterium infantis inside hydrogels could prolong their survival in fermented milkless beverages. The starter culture Streptococcus thermophilus was used to obtain fermented nonmilk beverages: oat, oat-banana, and oat-peach. The biota of beverages were supplemented with Bifidobacterium infantis cells, free and immobilized, in three types of spherical hydrogel particles: microcapsules with a liquid and gelled core, microbeads of 0.5 mm diameter, and beads of 2.5 mm diameter. As a carrier material, low-methoxylated pectin and alginate were used. Microbeads and microcapsules were obtained using extrusion techniques: vibrating and electrostatic method, and beads were obtained using manual method with a syringe. A significantly lower decrease in the count of cells immobilized in hydrogels compared to free cells was observed during storage of fermented beverages at 4°C. Microcapsules were more effective compared to microbeads in terms of bacterial cells protection. The observed effect was better for higher biopolymer concentration. The highest survival of the strain was noted in cells immobilized in low-methoxylated pectin beads of 2.5 mm diameter. Supplementing the biota of fermented beverages with microencapsulated bacteria did not negatively affect the overall sensory quality of beverages during the entire storage period.